What software engineering has to offer to agent-based social simulation - Siebers, Peer-Olaf; Klügl, Franziska (Springer, 2017)
In simulation projects it is generally beneficial to have a toolset that allows following a more formal approach to system analysis, model design, and model implementation. Such formal approaches are developed for supporting a systematic proceeding by making different steps explicit as well as by providing a precise language to express the results of those steps, documenting not just the final model but also intermediate steps. This chapter consists of two parts: The first gives an overview of which tools developed in Software Engineering can and have been adapted to agent-based social simulation; the second part demonstrates with the help of an informative example how some of these tools can be combined into an overall structured approach to model development.